The Influence of Product Usage Frequency, Product Prices, and Disclosures of Bills on Consumers' Installment Payment Emotions - Huang, Li-Shia; Chen, Yi-Ling (Xing Xiao Ping Lun, 2012)
In order to stimulate consumption, many firms allow consumers to pay by installment, even for small or medium bills. Prior research about installment usually based on financial perspective and focused on large bills, which may not clearly explain consumers' psychological factors of installment on small or medium bills. This study explores the effects of different products frequency of use, product prices, and disclosures of bills on consumers' installment payment emotions. In this research, 311 subjects participated in a 2*2*2 between subject experiment. The ANCOVA test suggests that low frequency of product use and high price had negative effects on the payment emotions. Credit and debt attitude and retention time of money value had some moderating effects. Marketing implications and future research directions are also provided. [PUBLICATION ABSTRACT]